Variant in the sequence of the LINGO1 gene confers risk of essential tremor - Stefansson, Hreinn (2009)
We identified a marker in LINGO1 showing genome-wide significant association (P = 1.2 × 10(−9), odds ratio = 1.55) with essential tremor. LINGO1 has potent, negative regulatory influences on neuronal survival and is also important in regulating both central-nervous-system axon regeneration and oligodendrocyte maturation. An increase in the number of fusiform swellings of Purkinje cell axons in LINGO1 knockout models highlights the potential role of LINGO1 in essential tremor pathophysiology.